Drugs Behaviour and the Brain Chemistry - Wagner, Henry N. (Defence Science Journal, 2013)
Drugs affect the hundreds of billions of molecules that make up our brains, our 'universe within'. Molecules serve as chemical 'messengers' which circulate through the body until they encounter other molecules on the surface of the cells which fit their specific configuration. The molecules carrying information- are called 'neurotransmitters'. They react with other molecules called 'neuroreceptors', which modify the response to the information in the neurotransmitters by interacting the way a key fits into a lock. Thus, information is passed from cell to cell. Molecular 'recognition sites' integrate the individual cells of the body, and together they make the person a unique individual